Inhibition of Urea Hydrolysis of Human Urine using Lactic Acid from Selected Fruit and Vegetable Waste Fermentation - Khamala, Tabitha Nekesa; Mungai, George N.; Mwangi, Erastus K. (African Journal of Science, Technology and Social Sciences, 2025)
In Kenya, enormous amounts of fruit and vegetable waste are improperly disposed of, contributing to environmental pollution and odour. Meanwhile, urine contains nitrogen that can be used as a fertiliser, but its utility is impeded by urea hydrolysis, which causes a rise in pH, nitrogen loss, and ammonia formation. This study investigated the potential of lactic acid fermentation utilising fruit and vegetable waste to prevent urea hydrolysis, enabling nitrogen recovery. Anaerobic fermentation of selected fruit and vegetable waste was carried out in an incubator at a regulated optimum temperature of 37°C for 72 hours. The lactic acid formed was then utilised to treat urine samples for 4, 7, and 10 days. To assess urea hydrolysis inhibition, total nitrogen content was measured using the Kjeldahl method, and pH monitored with a pH meter. The results showed a considerable decrease in the stabilised urine’s pH, ranging from 6.1 to between 3.6 and 3.9. The pH for the untreated urine rose to between 7.5 and 8.5 across the days. Statistical analysis using the one-way ANOVA indicated significant difference in the pH across the days (P = 0.047). The highest total nitrogen concentration for the stabilised urine was 2450 mg/L, after seven days of treatment, demonstrating urine stability and nitrogen preservation. The total nitrogen concentration for untreated urine was approximately 607 mg/L across the days, indicating clear nitrogen loss from the original 2643 mg/L obtained in fresh urine. One-way ANOVA test demonstrated a statistically significant fluctuation in TKN concentrations over treatment durations (P = 0.021). The findings showed that lactic acid significantly suppressed urease activity, making it a cheap, ecologically friendly alternative for urine stabilisation. The results showed the effectiveness of lactic acid obtained from fruit and vegetable waste in inhibiting urea hydrolysis in urine, hence, enhancing the recovery of nitrogen nutrient.